Biomechanical Effect of an Exposed Dental Implant’s First Thread: A Three-Dimensional Finite Element Analysis Study - Hudieb, Malik Ismail; Wakabayashi, Noriyuki; Abu-Hammad, Osama Abdullah; Kasugai, Shohei (Medical Science Monitor, 2019)
BACKGROUND The purpose of this study was to assess the effect of different exposure levels of a dental implant's first thread on adjacent bone stress and strain using the finite element analysis method. MATERIAL AND METHODS Three-dimensional models of 2 threaded implants and abutments with a mandibular bone segment were constructed to represent the covered (C) and exposed models. In the exposed models, the implant was first placed in the bone, and rotated around its axis a quarter-turn each time to simulate 4 different levels of first thread exposure at the mid-lingual side: Upper Flank (UF), Thread Crest (TC), Lower Flank (LF), and Thread Root (TR) models. Oblique forces were applied and analysis was performed. RESULTS Maximum compressive stress magnitude and distribution varied according to the exposed thread profile. In the exposed group, peak stress ranged from 136 MPa to 197 MPa in TC and LF models, respectively, compared to 141 MPa in C model. In LF, UF, and C models, peak stress was observed at the mid-lingual side of the crestal region, while in TC and TR models, peak stress shifted distally in accordance with thread profile. However, alveolar bone volumes which exhibited compressive microstrain levels within the physiological loading and maintenance windows were relatively close in all models. CONCLUSIONS Results suggest that the exposed thread profile influences stress and strain outcomes in the adjacent bone; however, this influence is only limited to a small region around the exposed thread.